Reframing the Civic University
XIII, 177 p. 12 illus.
Keywords: This book addresses the need for a comprehensive reappraisal of what it means to be a ‘civic university’. For two decades the ‘civic’ agenda has been driven by a concern with economic impact and regional economic development. While recognising the importance of these aspects of universities’ civic influence, there is a need to more comprehensively outline how universities can and should make a difference across a wide spectrum of place-based activity, against a background of intensifying global social and environmental challenges. Rooted in collaborative work by the Civic University Network and community-based partners, the book provides a clear logical framework that universities and their partners can use to examine the extent of their civic activities, but also challenges them to use that framework as a starting point for deeper reflection and engagement. It celebrates the actions universities have taken to respond to communities’ needs, and encourages them to think more rigorously about what they can do in the future, and how they can become more accountable to the communities they serve. The book is an essential read for university leaders, academics involved in public engagement, and civic leaders and representatives who wish to develop closer engagement with their local universities. Julian Dobson is Senior Research Fellow at the Centre for Regional Economic and Social Research, Sheffield Hallam University, UK. He has worked in academia, consultancy and journalism and is known as a writer and conference speaker. Ed Ferrari is Director of the Centre for Regional Economic and Social Research, Sheffield Hallam University, UK. He has wide ranging knowledge and practical experience of local and regional policymaking and collaboration across academic, policymaking, practitioner and private sector organisations. .